Personalization (Personomen) Function in the Text Space of Dmytro Dontsov’s Works: Opposition Aspect (Linguostylistic Studies, 2017)
The article highlights the issue of opposition of national and liberal views concerning concepts of land, glory, power, heroism and «the spirit of the ruling caste». The author argues that the names of personalities are the bearers of political, philosophical, culturological, evaluative information and draws the conclusion that the historical and political background fully reproduces certain events or situations. The in-depth analysis of the Dmytro Dontsov’s works revealed that the author lays emphasis on the positive facts of history, depicting the courage of Ukrainians, their militant spirit and the unbridled zeal in advocating the truth and their own land. In addition, analyzing the problems of Ukrainian reality, the author contributes to the formation of the state-centered views among readers. The opposition aspect of the personalities’ names (personomen) in scientific-journalistic and journalistic texts allows us to understand the author's position, who saturates the reader with information visualizing the intellectual background of the epoch. The study confirms that the technique of opposing personalities’ names is quite an effective means of characterizing the language picture of the world.
Keywords: names of personalities; opposition of views; scientific-journalistic and journalistic texts; Dmytro Dontsov